Early Cervical Lesions Affecting Ovarian Reserve and Reproductive Outcomes of Females in Assisted Reproductive Cycles - Yang, Qiyu; Hu, Juan; Wang, Meng; Li, Zhou; Huang, Bo; Zhu, Lixia; Xi, Qingsong; Jin, Lei (Frontiers in Oncology, 2022)
To estimate the effects of early cervical lesions (ECL) on female reproductive function and IVF/ICSI cycle outcomes, a retrospective cohort study involving 111 infertile women from 2014 to 2019 was performed. Thirty-seven women with a history of ECL and seventy-four controls, undergoing IVF/ICSI cycles, were included in the ECL group and comparison group respectively. Demographic characteristics, ovarian reserve, and IVF/ICSI cycle outcomes of both groups were collected. Basal serum FSH level, AMH level, AFC, number of oocytes retrieved and matured, normal fertilization rate, embryo available rate, blastocyst formation rate, implantation rate, pregnancy rate, and cumulative live birth rate (CLBR) were assessed and compared. We observed that while both groups were similar concerning baseline features, significantly more women in the ECL group were diagnosed as poor ovarian response (POR), compared with those in the comparison group (27.0% vs. 10.8%, P=0.003). The pregnancy rate and LBR for a complete cycle were both significantly lower in the ECL group (38.5% vs. 58.8%, P=0.021; 28.9% vs. 48.2%, P=0.025, respectively). The conservative and optimal CLBRs for up to four complete cycles in the ECL group were also lower than those in the comparison group (40.5% vs. 55.4%, P=0.140; 45.9% vs. 67.6%, P=0.028). Longer time intervals (over one year) between ECL diagnosis/treatment and assisted reproductive technology (ART) cycle start negatively affected the pregnancy rate and LBR. In conclusion, female patients with ECL history seemingly have a lower ovarian reserve, reduced pregnancy rate, and decreased live birth rate (LBR), compared with age-matched women undergoing IVF/ICSI.